PENINGKATAN KEMAMPUAN HAFALAN ASMAUL HUSNA MELALUI MEDIA AUDIO VISUAL DI SD NEGERI 02 CAMPAGO GUGUAK BULEK, KECAMATAN MANDIANGIN KOTO SELAYAN, BUKITTINGGI - Wirman Hanizon (El-Rusyd, 2021)
Asmaul Husna are good names for Allah. In this case, the memorization of Asmaul Husna is a material given to elementary school children with a rote system. In fact, it is not only carried out in elementary schools but has also been contested. Where in memorizing Asmaul Husna as many as 99 good names for Allah, it seems that students have difficulty. To overcome the problem of memorizing these students against the dhikr of Asmaul Husna, audio-visual media were used. In this audio visual media, students can also see what they read. Thus, it is hoped that students can understand what they read and in the end they can memorize it as well.